A lateral electric field inhibits gel-to-fluid transition in lipid bilayers. Issue 34 (19th August 2022) - Thomas, Nidhin; Agrawal, Ashutosh
Abstract : We report evidence of lateral electric field-induced changes in the phase transition temperatures of lipid bilayers. Abstract : We report evidence of lateral electric field-induced changes in the phase transition temperatures of lipid bilayers. Our atomic scale molecular dynamics simulations show that a lateral electric field increases the melting temperatures of DPPC, POPC and POPE bilayers. Remarkably, these shifts in the melting temperatures are only induced by lateral electric fields, and not normal electric fields. This mechanism could provide new mechanistic insights into lipid–lipid and lipid–protein interactions in the presence of endogenous and exogenous electric fields.